“Chapa” quente : recursos de aprendizagem coletiva para explorar fenômenos térmicos - Paz, Taiala Patrícia Cerqueira da (2019)
Physics teaching has been taking place far from the reality of students in general. Lack of knowledge of thermal phenomena and their relationship with everyday life makes it difficult to correctly acquire skills and abilities in this area, as well as to solve simple everyday problem situations. Thus, this paper proposes to present a didactic sequence on Thermology and Thermometry based on Peer Instruction and Just-in-Time Teaching techniques, in high school classes. The active learning methodology was used for the development of the activities because we believe that the student becomes responsible for the learning process, being not only a receiver of information, but also an autonomous and participative subject. Thus, they had online access to reading and conceptual testing tasks, as well as being stimulated to produce online content such as video lessons, experiments such as a Thermoscope and Thermal Bag, as well as discussion texts. All this didactic material produced resulted in the Educational Product of this work and is available on a website. The research was quite satisfactory, as shown by the quantitative results in graphs, with advances in the elaboration and resignification of the physical concepts studied; as well as qualitative results, observed by the improvement of interaction and union of the class among themselves and with the teacher.